Investigation of a Radiation Pattern Frequency Dependence of a Subarrayed Slotted Waveguide Antenna Using CAD Ansys HFSS - V. G. Koshkid’ko; M. M. Migalin (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. A resonant slotted waveguide antenna allows providing broadside radiation, which coincides with the normal line to the longitudinal axis of the array. Such an antenna can be well-matched in a very narrow frequency band. Even a slight deviation from the operating frequency leads to a significant distortion of the radiation pattern. In this regard, the distortion of the radiation pattern is becoming an urgent task.Aim. The main objective of this work is to preserve the radiation pattern of the resonant slotted waveguide antenna with longitudinal slots in the broad face in operating bandwidth.Materials and methods. Subarraying was performed to preserve the undistorted radiation pattern of the slotted waveguide antenna array in the operating bandwidth. The antenna model and its directional properties were analyzed in CAD Ansys HFSS using Visual Basic Scripting Edition macros.Results. Three slotted waveguide antennas’ models, consisting of two, four, and eight subarrays were developed in Ansys HFSS CAD. The effect of subarraying on the radiation pattern at the center frequency and the upper and the lower operating frequencies is studied. It is shown that the growing number of subarrays leads to a more stable radiation pattern in the operating bandwidth.Conclusions. Full-wave electromagnetic simulations have shown that subarraying of a resonant slotted waveguide antenna is a useful measure that preserves undistorted radiation pattern in the operating frequency band. Usage of Visual Basic Scripting Edition macros allows to minimizing the time spent creating a model in CAD Ansys HFSS.